Stressors and Violence Among LGBTQ in Intimate Partner Relationships - Sanchez, Rhymelyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the stressors and violence experienced by LGBTQ individuals in intimate partner relationships, particularly among LGBTQ criminology students of Sorsogon College of Criminology, Inc. It was anchored on the Minority Stress Model, Maslow’s Hierarchy of Needs, Erikson’s Psychosocial Theory of Development, and the Input-Process-Output Model. A qualitative phenomenological research design was used to describe the lived experiences of the participants. Ten LGBTQ students who had experienced intimate partner violence and minority stressors were selected through purposive and snowball sampling. Data were gathered through open-ended and unstructured interviews, observation, and expert validation, with interviews conducted in a safe and private setting and transcribed verbatim. The data were analyzed using Colaizzi’s process and selective coding. Findings revealed two major themes: forms of violence and minority stressors. The forms of violence included physical, emotional, psychological, sexual, and economic or financial violence, which were marked by control, coercion, manipulation, boundary violations, and dependency. The minority stressors included hate crimes, discrimination, identity concealment, and internalized homophobia, which contributed to emotional distress, damaged self-worth, social isolation, fear of exposure, and strained relationships. The study concluded that stressors and violence in LGBTQ intimate relationships are interconnected and require stronger protection, inclusive support systems, awareness programs, counseling, legal assistance, safe spaces, and institutional interventions. The proposed seminar, “Unveiling the Struggles: Exploring Stressors and Violence in LGBTQ Intimate Relationships,” aims to promote awareness and resilience. The study supports SDG 3, SDG 4, SDG 5, SDG 10, and SDG 16 by addressing well-being, inclusive education, gender-related protection, reduced inequalities, and stronger justice-oriented institutions. Its sustainability impact lies in strengthening public health, educational, social, institutional, community, and governance responses to LGBTQ intimate partner violence.